2018
DOI: 10.1177/1464420718803126
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on dry sliding frictional and wear characteristics of SiC and red mud reinforced Al2024 matrix hybrid composites using Taguchi's approach

Abstract: In this study, frictional and wear behavior of Al2024/SiC/red mud hybrid composites processed by stir casting route has been investigated under dry sliding conditions. Further, influence of parameters, namely red mud fraction (5–20 wt%) and particle size (37–125 µm), applied load (10–40 N), sliding distance (3000–6000 m), sliding velocity (0.5–2.0 m/s), and their interaction terms on multiresponse characteristics has been examined by employing Taguchi's approach. The wear behavior of hybrid Al composites has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Singh and Chauhan [4] investigated the wear performance of the aluminum matrix composites, namely, aluminum alloy together with silicon carbide and red mud prepared by stir-casting method. Statistical approach (Taguchi) is involved for their investigations, and parameters are preferred as percentage of red mud fraction, particle size and applied load, sliding distance, and sliding velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Singh and Chauhan [4] investigated the wear performance of the aluminum matrix composites, namely, aluminum alloy together with silicon carbide and red mud prepared by stir-casting method. Statistical approach (Taguchi) is involved for their investigations, and parameters are preferred as percentage of red mud fraction, particle size and applied load, sliding distance, and sliding velocity.…”
Section: Introductionmentioning
confidence: 99%
“…This was in agreement with previous studies which showed a higher wear rate of the MMCs at higher contact loads. 49,50 The significantly higher material loss of the samples with a higher weight fraction of Al 2 O 3 nanoparticles than the optimum level showed that the effects of excessive weight fraction of nanoparticles in the composite were more detrimental than having an insufficient weight fraction of nanoparticles in the composite. It can be said that agglomeration in samples with a higher weight fraction of nanoparticles than optimal weight fraction reduced the strength of samples.…”
Section: Effect Of Load On Wear Loss Of the Samplesmentioning
confidence: 98%
“…The wear resistance is higher when reinforcement is added due to the formation of hard and resistant layer on the wear surface of composites and reduced frictional coefficient is achieved owing to lower fictional contact between sliding surfaces. 72 Singh and Yadav studied the wear characteristics of different weight percent values of RM-filled epoxy functionally graded composite. The sliding wear characteristics significantly enhanced by adding RM particles to the composites, as smaller grooves are seen at the surface of composites.…”
Section: Effect Of Red Mud On Tribological Propertiesmentioning
confidence: 99%